Anatomical venous landmarks for division of the distal pancreas: Implications for pancreatic resection - Chandrakumarsing Anauth; Ruvashni Naidoo; Lelika Lazarus (Elsevier, 2023)
Introduction: Resection of the pancreas is done for benign and malignant diseases. Distal pancreatectomy (DP) is defined as a resection of the body and tail of the pancreas which lie to the left of the superior mesenteric vein (SMV). The inferior mesenteric vein (IMV) is traditionally described to be draining into the splenic vein. This study aimed to determine the relationship of the IMV with respect to the distal pancreas to illustrate how it can be implemented as a landmark, especially to define the tail of the pancreas for parenchyma-sparing distal pancreatic resection. Methods: This study included the dissection of 50 cadavers, which were obtained from the Department of Clinical Anatomy at a higher education institution in South Africa. The sex of the cadavers and the drainage pattern of the IMV were documented, along with the distance from the confluence of the SMV and splenic vein. Descriptive statistics were used to summarise the results. [Ethical Approval Number: BE465/18]. Results: Wide variation in the drainage patterns of the IMV was noted, with overall 48% draining into the SMV, 36% in the splenic vein and the rest at the confluence of the SMV and splenic vein. The preferential pattern of the IMV draining into the SMV was more prominent in males, with females having been evenly distributed between the SMV and splenic vein. The distances measured were not statistically significant owing to the restricted sample size and outliers noted during data collection. Conclusion: This study confirmed the wide variation in drainage patterns of the IMV. Literature regarding limited pancreatic resections and the rate of pancreatic endocrine failure is increasing. The measured distances show some promise in using the IMV as a landmark for dividing the pancreas when it is draining directly into the splenic vein. However, larger cohort studies are required to validate this hypothesis.